Effect of Host Plants on Predator Prey Relationship between Predatory Bug, Orius laevigatus (Fiber) [Hemiptera: Anthocoridae] and Tobacco Whitefly, Bemisia tabaci (Gennadius) [Homoptera: Aleyrodidae] - Abdul-Jalil Hamdan; Iyad Abu-Awad (مجلة جامعة النجاح للأبحاث العلوم الطبيعية)
This study was conducted to investigate the effect of host plants on the predatory bug, O. laevigatus. Tobacco whitefly, B. tabaci was offered on tomato and eggplant leaf discs as food source for the predator in the laboratory at temperature of 25±1?C, 75±5% R.H, and 16 L: 8 D photoperiod regime. Results showed that adults of O. laevigatus were able to feed on both eggs and larval instars of B. tabaci maintained either on tomato or eggplant. O. laevigatus preferred significantly (P < 0.05) feeding on B. tabaci eggs more than on larvae. Thus, the average daily consumption of adult O. laevigatus was 30.44 eggs and 3.2 larvae of B. tabaci infesting tomato but that on eggplant was 27.6 eggs and 2.45 larvae. In addition, fertility of O. laevigatus females was significantly greater when the predator fed on B. tabaci reared on tomato than that on eggplant. Thus, the average total nymphs produced by each O. laevigatus female fed on B. tabaci infestation were 64.5 when offered on tomato leaf discs, and 34.8 when offered on Eggplant leaf discs. Therefore, further laboratory and field studies were suggested to be carried out on practical use of O. laevigatus as a biocontrol agent against B. tabaci as a pest.